A new method to determine the synergistic effects of area ratio and microstructure on the galvanic corrosion of LAS A508/309 L/308 L SS dissimilar metals weld - Okonkwo, Bright O.; Ming, Hongliang; Wang, Jianqiu; Han, En Hou; Rahimi, Ehsan; Davoodi, Ali; Hosseinpour, Saman (Journal of Materials Science & Technology, 2021)
The synergistic effects of area ratio and microstructure on the galvanic corrosion of A508/309 L/308 L dissimilar metals weld (DMW) are studied by a multi-analytical approach. It was demonstrated that decreasing the anode/cathode surface area ratio obviously enhances the corrosion rate of A508, both locally and globally. Deeper analyses of the AFM results enabled quantitative comparison of the corrosion behaviour of the different surface constituents. It was revealed that in the galvanic interaction of the DMW, the grain refined region corrodes most, followed by the partial grain refined region and base metal matrix of the A508, respectively. The electrochemical localization index (LI) estimation method and AFM analysis both confirmed the presence of a mixed (localized and uniform) corrosion phenomenon occurring on the surface of the A508 anode metal in the galvanic interaction of the dissimilar metals. Finally, the degree of synergism equation was utilized to describe the synergistic effects of anode/cathode area ratio and the microstructure of the samples on the galvanic corrosion of LAS A508/309L/308L SS DMW.
CRIS-Team Scopus Importer:2020-12-11
Keywords: AFM; Galvanic corrosion; Inclusion; Low alloy steel; SEM; Stainless steel